Obstetric and Gynecologic Resident Ultrasound Education Project: Is the Current Level of Gynecologic Ultrasound Training in Canada Meeting the Needs of Residents and Faculty?. (7th August 2015) - Green, Jessica; Kahan, Meldon; Wong, Suzanne
Abstract : Objectives: Ultrasound is a critical diagnostic imaging tool in obstetrics and gynecology (Ob/Gyn). Obstetric ultrasound is taught during residency, but we suspected a gap in Gyn ultrasound education. Proficiency in Gyn ultrasound allows real‐time interpretation and management of pelvic disease and facilitates technical skill development for trainees learning blinded procedures. This study sought to evaluate ultrasound education in Canada's Ob/Gyn residency programs and assess whether residents and physicians perceived a need for a formalized Gyn ultrasound curriculum. Methods: We distributed a needs assessment survey to residents enrolled in Canadian Ob/Gyn residency programs and to all obstetrician/gynecologists registered as members of the Society of Obstetricians and Gynaecologists of Canada. Residents were asked to specify their current training in ultrasound and to rate the adequacy of their curriculum. All respondents rated the importance of proficiency in pelvic ultrasound for practicing obstetrician/gynecologists as well as the perceived need for formalized ultrasound training in Ob/Gyn residency programs. Results: Eighty‐two residents and 233 physicians completed the survey. Extents and types of ultrasound training varied across residency programs. Most residents reported inadequate exposure to Gyn ultrasound, and most residents and physicians agreed that it is important for obstetrician/gynecologists to be proficient in Gyn ultrasound and that the development of a standardized Gyn ultrasound curriculum for residency programs is important. Conclusions: Current ultrasound education in Ob/Gyn varies across Canadian residency programs. Training in Gyn ultrasound is lacking, and both trainees and physicians confirmed the need for a standardized Gyn ultrasound curriculum for residency programs in Canada.